Deskripsi Sistem Kekerabatan dan Sapaan Pada Etnik Batak Simalungun - Sihotang, Kristina; Sinaga, Warisman; Purba, Asriaty R; Sinulingga, Jekmen; Herlina, Herlina (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
Penelitian ini berjudul